PERBANDINGAN HUKUM PENGATURAN PIDANA MATI DAN EKSEKUSINYA INDONESIA DENGAN JEPANG: Comparison of Legal Regulation and Execution of the Death Penalty: Indonesia and Japan - Winahyu Try Suryandary; Gandes Candra Kirana (AMICUS CURIAE, 2025)
The death penalty is one of the oldest forms of punishment recognized in both oral and written law and is still applied in Indonesia. This research aims to compare the regulation and implementation of the death penalty in Indonesia and Japan. This study identifies the problem concerning the similarities and differences in the legal framework and execution methods, as well as the strengths and weaknesses of each country’s approach. This research uses a normative-descriptive method with secondary data through literature study analyzed qualitatively. In Indonesia, the death penalty is regulated in the Criminal Code (KUHP) and other criminal laws, while its implementation refers to Law No. 2/PNPS/1964 and the Chief of Police Decree No. 12 of 2010. Its strength lies in the comprehensive legal basis in both substantive and procedural law, with execution carried out by a firing squad. Its weakness is the inconsistency of law enforcement despite the clear rules. In Japan, the death penalty is regulated in the Criminal Code and Criminal Procedure Code. Public support and the perception that capital punishment deters serious crimes are its strengths. However, the main weakness lies in its method of hanging, with the research findings and conclusion showing that each country reflects different social and political values in their approach.